Practice variation on use of antibiotics: An international survey among pediatric urologists. Issue 6 (December 2018) - Kim, Jin K.; Chua, Michael E.; Ming, Jessica M.; Braga, Luis H.; Smith, Grahame H.H.; Driver, Christopher; Koyle, Martin A.
Summary: Introduction and background: Although there is abundance in literature focusing on the use of prophylactic antibiotics for adult urological procedures, the evidence for using antibiotics following common pediatric urological procedures is limited with no specific guidelines for use. Consequently, current practices on antibiotic usage for common interventions may be variable among practicing pediatric urologists, lacking evidence-based support. Objective: The aim was to evaluate the current practice pattern on antibiotic usage for common interventions amongst pediatric urologists (PU) practicing in four English-speaking sectors of the world. Materials and methods: An anonymous survey of five scenarios with multiple choice options was disseminated to all active practicing members of the Pediatric Urologist of Canada (PUC) and Society of Pediatric Urology of Australia and New Zealand (SPUNZA), as well as all those attending the 2016 British Association of Pediatric Urology (BAPU) and 2017 American Association of Pediatric Urology (AAPU) meetings. The response for each scenario was summarized for overall practice pattern variation and the pattern for each sector was compared using the Fisher exact test. Results: A total of 126 respondents completed the survey (68.5% response rate) with at least a 65% response rate for each of the four sectors. The majority of respondents do not use antibiotics for indwelling urethral (46.8%) and suprapubic catheters (53.4%); however, they do give antibiotics for J-J stent placement (65.1%) and hypospadias surgery (84.9%), and use antibiotics after hypospadias surgery where catheters or stents are left indwelling (80.9%, 84.2%, respectively). Among those surveyed, the PUC members and AAPU PU demonstrated similar practice patterns which often significantly differed from that of SPUNZA members and BAPU attendees. Specifically, a significantly larger proportion of the North American pediatric urologists do not use antibiotics for common procedures compared with Australia, New Zealand, and the UK (Table). Discussion: In the absence of prospective studies in antibiotic use for pediatric patients to guide clinicians, there is a clear variability among sectors in the use of antibiotics for most clinical scenarios investigated. With increasing resistance patterns and possible adverse effects of antibiotics, it is important that the international pediatric urology community engage in discussions and collaborations to address this issue. Conclusion: Practice patterns in antibiotic usage amongst PU varies widely, some of which may be associated with their local "culture." There is a need to understand these differences and begin to standardize treatment in the hopes of increasing appropriate use of antibiotics internationally. Table Summary of responses for survey scenarios for each organization. Scenario PUC SPUNZA AAPU BAPU N P T N P T N P T N P T 1 20 (83.3%) 4 (16.7%) 0 (0.0%) 7 (21.2%) 20 (60.6%) 6 (18.2%) 15 (65.2%) 8 (34.8%) 0 (0.0%) 17 (37.0%) 26 (56.5%) 3 (6.5%) 2 20 (83.3%) 4 (16.7%) 0 (0.0%) 6 (18.2%) 23 (69.7%) 4 (12.1%) 18 (78.3%) 5 (21.7%) 0 (0.0%) 23 (50.0%) 21 (45.7%) 2 (4.3%) 3 19 (79.2%) 5 (20.8%) 0 (0.0%) 4 (12.1%) 27 (81.8%) 2 (6.1%) 13 (56.5%) 10 (43.5%) 0 (0.0%) 8 (17.4%) 38 (82.6%) 0 (0.0%) 4 7 (29.2%) 17 (70.8%) 4 (12.1%) 29 (87.9%) 1 (4.3%) 22 (95.7%) 7 (15.2%) 39 (84.8%) 5 10 (41.7%) 12 (50.0%) 2 (8.3%) 4 (12.1%) 21 (63.6%) 8 (24.2%) 4 (17.4%) 13 (56.5%) 6 (26.1%) 6 (13.0%) 14 (30.4%) 26 (56.5%) N = no antibiotics; P = prophylactic dose; T = therapeutic dose.